Patterns of scrotal pain in a hospital setting - Suman Chapagain (Society of Surgeons of Nepal, 2017)
Introduction: Scrotal pain is a common urological condition. Common causes of scrotal pain are testicular torsion, epididymitis, epididymo-orchitis and occasionally due to post vasectomy pain, varicocele, testicular trauma etc. The objective of our study is to review the different disease patterns in patients presenting with scrotal pain in a tertiary care hospital.